Systemic abnormalities in liver disease - Minemura, Masami (The WJG Press, 2009)
Systemic abnormalities often occur in patients with liver disease. In particular, cardiopulmonary or renal diseases accompanied by advanced liver disease can be serious and may determine the quality of life and prognosis of patients. Therefore, both hepatologists and non-hepatologists should pay attention to such abnormalities in the management of patients with liver diseases.